Dynamics of autoagressive behavior in youth in the trajectory of borderline personality disorder - A. A. Kuleshov; E. S. Krylova; A. A. Beburishvili; V. G. Kaleda (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
Objective: to determinate the clinical and psychopathological characteristics of autoagressive behavior (AB) in youth in the trajectory of borderline personality disorder (BPD) with determinate relathionship between each other, further dynamics and prognosis.   Material and methods. Clinical-psychopathological (61 patients), follow-up (55 patients), retrospectively and psychometric methods, 116 patients males and females with autoagressive behavior (AB) in youth in the trajectory of BPD were clinically observed in outpatiently and psychiatric hospital. Patients with AB were divided into three equal groups: 1 — Non-suicidal self injurance (NSSI); 2- suicidal attempts (SA); 3- NSSI with SA.   Results. Correlations have been established between the original typology of BPD and AB: in the clinical group — impulsivity (64%) and demonstrative (24 %) AB of BPD type I (“affective storm”), addictive (44.4 %) in type II (“addictive adrenalin addiction”) — depersonalization (51,9%) and self-torturing (11,1 %) in type III (“cognitive distortions and disorders of self-identification”). In the follow-up group was noted transformation of main variants AB towards addictive behavior (56,4 %).   Conclusion and findings. The formation of auto-aggressive behavior in adolescence and in the trajectory of BPD is due to the interaction of the age factor with the main personality traits of BPD — impulsivity, affective instability, impaired identification, alexithymia and leading psychopathological syndromes. A high association of NSSI with suicidal activity was confirmed, and high suicidal risk for BPD was revealed not only in adolescence, but also after it has passed. The data obtained will contribute to the future study of autoagressive behavoir in personality disorder and for the creation of new therapeutic and social models of patients.